Surgical robotics for esophageal cancer. Issue 1 (9th May 2018) - Grimminger, Peter P.; van der Horst, Sylvia; Ruurda, Jelle P.; van Det, Marc; Morel, Philippe; van Hillegersberg, Richard
Abstract: We present an update on robotic techniques and their advantages and use in esophageal cancer surgery. Recent work has shown tremendous progress in robotic‐assisted minimally invasive esophagectomy (RAMIE) and lymphadenectomy for esophageal cancer, as well as benefits of robotic surgery in high upper esophageal tumors and T4b disease. We discuss the different RAMIE techniques, especially for intrathoracic anastomosis. The ongoing ROBOT trial had demonstrated superiority of robotic esophageal cancer surgery over open esophagectomy. There are various putative technical advantages of RAMIE over minimally invasive esophagectomy, which need to be proven in future trials. Abstract : Recent work has revealed tremendous progress in robotic‐assisted minimally invasive esophagectomy (RAMIE) and lymphadenectomy for esophageal cancer, as well as benefits of robotic surgery in high upper esophageal tumors and T4b disease. We discuss different RAMIE techniques, especially for intrathoracic anastomosis. There are putative technical advantages of RAMIE over minimal invasive esophagectomy, which need to be proven in future trials.